Magyar államtér és külpolitikai kényszer - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2015)
The territorial changes that defined the 20th century history of Hungary, the most important event of which was the Treaty of Trianon, defined a continuous inescapable path for Hungarian foreign and military policy. This geopolitical factor was not only true for the peace treaty, but was also relevant to the turn of the century, the first years of World War I, Mihály Károlyi’s term as prime minister, the 1919 far-left dictatorship, and to the subsequent war. The territorial changes, especially the dismemberment of the Kingdom of Hungary, had caused trauma to the nation. This historically detectable shock of mass psychology that pervaded the Hungarian nation posed a constant inescapable path for Hungarian foreign and military policy between 1918 and 1945. Accordingly, there is a close relationship between the territorial changes and the trends of foreign policy. In addition, the changes in the state territories in the Carpathian Basin in the first half of the 20th century fit into the trends of European political geography. The present study discusses this pressure from political geography and geopolitics as a political factor.